Engage, Play, Learn: A Systematic Literature Review on the Impact of Gamification on Young Learners’ English Skills - Hamuddin, Budianto; Priambada, Jewine Saragih; Indarwati, Indarwati; Sakka, Wahyuni; Anugrah, Muh. Ridha (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
This systematic literature review investigates the impact of gamification on young learners’ English language skill acquisition, addressing a research gap in understanding its specific contributions to engagement, motivation, and academic outcomes. By analyzing 26 peer-reviewed articles published between 2019 and 2024, sourced from Crossref, Scopus, and Semantic Scholar, this study categorizes findings into four themes: learner autonomy and motivation, vocabulary mastery, classroom participation and academic achievement, and intrinsic motivation. The results reveal that gamification significantly enhances learner autonomy and intrinsic engagement by integrating game-like elements such as leaderboards and progress trackers. Vocabulary acquisition benefits from contextualized and repetitive gamified activities, which improve retention and recall. Gamification also fosters classroom participation and academic success by creating inclusive and interactive learning environments, often aligned with cognitive frameworks like Bloom’s Taxonomy. However, the review identifies challenges such as inconsistent methodologies, technical limitations, and the novelty effect, which can influence the sustainability of gamification’s benefits. Despite these limitations, this study underscores gamification’s transformative potential in fostering dynamic, learner-centered environments that align with modern educational goals. The findings emphasize the need for thoughtfully designed gamified strategies that address diverse learner needs while promoting intrinsic motivation and sustained engagement. Future research should focus on longitudinal studies, the differential effects of competitive and collaborative gamification, and the integration of emerging technologies like AI and VR to further optimize gamified language education. These insights provide a foundation for innovative curriculum development and policy-making in education.